The effect of trimetazidine on ventricular repolarization indexes and left ventricular diastolic function in patients with coronary slow flow. Issue 5 (August 2016) - Suner, Arif; Cetin, Mustafa
Abstract : Objectives: Coronary slow flow (CSF) is associated with an increased incidence of adverse cardiovascular events. Previous studies have shown increases in P wave dispersion, QT dispersion, and the Tp-e/QT ratio, and a prolonged Tp-e interval, as well as left ventricular diastolic dysfunction in patients with CSF. We aimed to examine the effect of trimetazidine (TMZ) on these arrhythmia predictors and diastolic function of the left ventricle. Methods: Our study included 30 patients with CSF and 30 individuals with normal coronary arteries. Twelve-lead ECG and echocardiography were used to evaluate patients before and 4 weeks after treatment with TMZ. Results: Compared with the control group, corrected Pd (29.3±9.1 vs. 22.9±11.6, P =0.022), corrected QT dispersion (32.3±11.1 vs. 27.4±6.8, P =0.032), corrected Tp-e interval (103.1±18.6 vs. 93.4±11.5, P =0.017), and Tp-e/QT ratio (0.236±0.03 vs. 0.210±0.02, P =0.001) were significantly longer, and the E / A ratio (0.905±0.16 vs. 0.986±0.12, P =0.037) and the mean E m / A m ratio (0.918±0.19 vs. 1.095±0.20, P =0.006) were lower in patients with CSF. Corrected Pd, corrected Tp-e interval, and the Tp-e/QT ratio were significantly decreased (29.3±9.12 vs. 22.5±9.20, P =0.022; 97.3±16.6 vs. 88.2±16.4, P =0.031; 0.22±0.03 vs. 0.20±0.31, P =0.042 respectively), and left ventricle mitral annular mean E m / A m velocity was significantly increased (0.918±0.19 vs. 1.095±0.20, P =0.017) after treatment with TMZ. Conclusion: CSF may be related to increased P wave and QT dispersion, a prolonged Tp-e interval, and Tp-e/QT ratio, in addition to impaired diastolic filling. TMZ may be useful in restoring these findings.